Highly adherent essential oils compositions for the prevention and complex treatment of ARIs in pre-school children - I.V. Sergeeva (LCC «Medicine-Inform», 2022)
I.V. Sergeeva Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation Aim: to assess the efficacy of the composition of natural essential oils (inhaler patch) for the prevention and complex treatment of acute respiratory infections (ARIs) in pre-school children. Patients and Methods: this prospective study enrolled 102 children aged 3-7 attending kindergarten. The study was conducted simultaneously in four groups of children attending pre-schools (study and control groups, respectively). Study group children received passive inhalations of essential oils (inhaler patches), i.e., in combination with complex treatment for ARIs (group 1) or as a preventive measure after contact with sick children (group 3). Control group children (groups 2 and 4) did not receive passive inhalations. The rate of ARIs, disease severity, fever duration, catarrhal period duration, and inhaler patch tolerability were assessed. Results: in children who used inhaler patch to prevent ARI but still got sick (group 3), fever duration was 1.5 days (i.e., 2.3 days s horter than in group 4) irrespective of age. The number of sick children in group 3 was 2.2-times lower than in group 4. The disease was mild, not associated with any complications, and characterized by a shorter duration of the catarrhal period. In group 1 (compared to group 2), body temperature was less than 38°C, and more rapid rhinorrhea, nasal congestion, and cough relief were reported. Conclusions: our findings, in combination with the lack of adverse effects, allow us to recommend an inhaler patch to prevent ARIs during epidemics or seasonal peaks in pre-schools as a highly adherent entity characterized by excellent safety, no addiction, and long-term use. Keywords: prevention, ARIs, essential oils, children, efficacy, inhaler patch. For citation: Sergeeva I.V. Highly adherent essential oils compositions for the prevention and complex treatment of ARIs in pre-school children. Russian Journal of Woman and Child Health. 2022;5(1):58-62 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-58-62.